PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN EKONOMI DENGAN BELANJA MODAL SEBAGAI VARIABEL INTERVENING - Hartono, Meyzi Heriyanto, Febri Yuliani (Universitas Riau, 2020)
Effect of Financial Performance on Economic Growth with Capital Expenditures as Intervening Variables. This study aims to examine and obtain empirical evidence of the direct influence of the financial performance of local governments as measured by the ratio of the degree of fiscal decentralization, fiscal dependence, financial independence, effectiveness of local own revenue (PAD), and the level of contribution of BUMD to the ratio of capital expenditure allocation. This research uses a quantitative research method approach. The source of the data used is secondary data in the form of financial statements of regency / city governments throughout Riau Province in 2011 s.d. 2017. Data analysis techniques used path analysis with the program Eviews. The population of this research is all regency / city regional governments in Riau Province in 2011-2017. The results of this study indicate that financial performance simultaneously influences the allocation of capital expenditure and partially, the ratio of fiscal dependence and contribution of BUMD has a positive effect on the allocation of capital expenditure, while the ratio of the degree of decentralization, financial independence and effectiveness of local own revenue (PAD) do not affect the allocation capital expenditure. Capital expenditure allocation does not affect economic growth. Likewise, capital expenditure allocation does not have a mediating effect on the relationship of financial performance to economic growth.